PENGARUH PENGERASAN MATA GERGAJI DAN POLA PENGGERGAJIAN TERHADAP KARAKTERISTIK PENGGERGAJIAN KAYU KARET - Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This article presents study result on sawing characteristics of rubberwood (Havea brasiliensis Muell. Arg.) subjected to different cutting edge hardness and sawing pattern. The material used in study comprised 40 logs with length 1.30 m and diameter ranging from 13. 75 to 26.00 cm. Half of these logs were sawn with full stellite cutting edge and live sawing pattern. The rest were sawn with alternate stellite tiped cutting edge and half sawing pattern. The parameters studied in sawing process consisted of power consumption, feeding rate, recovery, productivity and the relationship between log diameter and log taper with recovery.The result of statistical analysis shows that sawblade with alternate stellite tiped consums less power compared with full stellite tiped, Meanwhile cutting edge hardness has no significant effect on feeding rate. The result also indicates that live sawing and half sawing pattern yield recovery as much as 35.9% and 40.9% respectively which was significantly dif- ferent each others. Finally, sawing productivity is not significantly affected by sawing pattern applied.